MATHEMATICAL MODELING OF STRATIFIED CURRENT OF BLOOD IN ABLOODVESSEL IN THE FORM OF A MODEL OF SEPARATE CURRENT OF TWO UNMIXED LIQUIDS IN A NARROWING CONIC TUBE - K.S. AKHVERDIEV; J.V. CHUDINOV; E.V. FOMICHEV; M.K. AKHERDIEVA (Advanced Engineering Research, 2008)
The problem of mathematical modelling of stratified blood current in a blood vessel has been soled in the paper on the basis of a model of separated current of two inmixed liquids in a narrowing conic tube. The influence of viscidity relations of strata on the types of speed distribution and relative expenses nave been evaluated.